Cognitive and Social Strategies to Deal With Anxiety in Speaking: Typical Strategies and Application - Milanrianto, Bayu Afkar; Permana, Dira; Ariani, Sri (Journal of Languages and Language Teaching, 2023)
This study aimed to reveal students’ strategies to deal with anxiety in performing speaking at Nurul Hakim Islamic Boarding School. The study was qualitative with case study design. The subjects of this study were eleventh grade students which were chosen through purposive sampling technique. The techniques of data collection were semi-structured interview and documentation. The data were analyzed through data reduction, data display and data verification and conclusion. Methodological triangulation technique was used to provide valid data. The result of this study showed there were five strategies used by eleventh grade students at Nurul Hakim Islamic Boarding school to deal with anxiety: Rehearsal, Preparation, Cooperation, Self-talk and Relaxation. From the five strategies, Rehearsal is the dominant strategies used by students to deal with speaking anxiety. Except Preparation and Relaxation, the other strategies were claimed effective to reduce anxiety. The five strategies were classified into two classifications: Cognitive strategy and Social strategy. Cognitive strategy involves Rehearsal and Preparation, while Social strategy involves Cooperation, Self-talk, and Relaxation. In this study, there were no strategies that represent the Metacognitive strategy.